2005
DOI: 10.1111/j.1525-1470.2005.22213.x
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Perianal Pyramidal Protrusion: Report of a Case and Review of the Literature

Abstract: Infantile perianal pyramidal protrusion is an important, relatively newly recognized condition, which is thought to be under-reported in the pediatric literature. Previous reports refer to these lesions as skin tags or skin folds. More recently, the name infantile perianal pyramidal protrusion has been suggested, based on the characteristic presentation of the lesion in prepubertal children, especially girls. Recognition of these lesions has many implications regarding proper diagnosis and management. They may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 5 publications
0
38
1
Order By: Relevance
“…According to Mérigou et al [7], constitutional IPPPs develop due to a weakness in the area of the perineum in females, which may explain why such conditions are seen mostly in girls. However, this hypothesis does not explain the presence of IPPPs in boys [8]. The congenital origin of IPPP is based on the discovery of these lesions in newborns and infants [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Mérigou et al [7], constitutional IPPPs develop due to a weakness in the area of the perineum in females, which may explain why such conditions are seen mostly in girls. However, this hypothesis does not explain the presence of IPPPs in boys [8]. The congenital origin of IPPP is based on the discovery of these lesions in newborns and infants [3].…”
Section: Discussionmentioning
confidence: 99%
“…Konta et al [3] suggested that congenital IPPP may be ‘a remnant of a projected tip of the urogenital septum’. In the acquired type, constipation seems to play a role as IPPP regresses after appropriate management [7, 8, 9]. However, it is not clear whether regression is due to the treatment of constipation or constipation is a consequence of the development of IPPP [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Infantile pyramidal protrusion usually resolves spontaneously within several weeks. 1,5,6 The pathogenesis of this entity is unknown, but may be a peculiar form of reaction, influenced by a constitutional weakness in the perineal region in females. 3 This weakness does not explain the occurrence in the male patient.…”
Section: Infantile Pyramidal Protrusion Localized At the Vulva As A Mmentioning
confidence: 99%